Angiographic patterns of drug‐eluting stent restenosis after treatment with drug‐coated balloon versus balloon angioplasty: Late lumen loss subgroup analyses of the PEPCAD‐DES study. Issue 4 (19th February 2016) - Rittger, Harald; Wöhrle, Jochen; Brachmann, Johannes; Hohenforst‐Schmidt, Wolfgang; Schlundt, Christian; Lonke, Sandra; von Cranach, Moritz; Markovic, Sinisa; Achenbach, Stephan; Waliszewski, Matthias
Abstract : Objectives: This report provides the results of additional late lumen loss (LLL) analyses the predefined subgroup of diabetics and post hoc analyses of selected lesion morphologies to further elucidate the efficacy of paclitaxel coated balloon (PCB) angioplasty (clinical trials identifier NCT00998439). Background: The PEPCAD‐DES trial revealed that in lesion LLL and the target lesion revascularization rate (TLR) were significantly reduced with PCB angioplasty as compared with plain old balloon angioplasty (POBA) in patients with drug‐eluting stent restenosis (DES‐ISR). Methods: A total of 110 patients with restenosis of Sirolimus‐ (SES), Everolimus‐ (EES), or Paclitaxel‐eluting (PES) stents in native coronary arteries were randomized 2:1 to receive treatment with PCB (72 patients) or POBA (38 patients). Results: In the PCB group, LLL did not differ for PES versus non‐PES lesions (0.46 ± 0.55 mm vs. 0.41 ± 0.65 mm, P  = 0.81). Moreover, there was no difference in LLL when PCB's were used in single and multiple layer DES‐ISR (0.35 ± 0.60 mm vs. 0.51 ± 0.63 mm, P  = 0.31). In contrast, patients treated with POBA for multilayer DES‐ISR were more likely to have significantly higher LLL as compared with single layer DES‐ISR (1.29 ± 0.76 mm vs. 0.65 ± 0.60 mm, P  = 0.02). There was no LLL difference between diabetics and non‐diabetics when treated with PCB angioplasty (0.46 ± 0.76 mm vs. 0.43 ± 0.54 mm, P  = 0.83). Conclusion: Our hypothesis generating results indicated that there were no differences in terms of LLL when PCB angioplasty was applied in subgroups of single versus multiple layer DES‐ISR and PES‐ISR versus non‐PES ISR. LLL was not higher in diabetic patients as compared with the their non‐diabetic counterparts when treated with PCB's. © 2016 Wiley Periodicals, Inc.